Case Report: Ultrasonographic and computed tomographic features of presumed gastric plasmacytoma (plasma cell tumor) with ulceration in two dogs - Seoro Park; Soyoung Jeung; Yewon Ji; Matti Kiupel; Matti Kiupel; Kichang Lee; Hakyoung Yoon (Frontiers in Veterinary Science)
Gastric plasmacytoma is rare in dogs, with only four previous reports providing limited descriptions of abdominal ultrasound (AUS) and computed tomography (CT) findings. This study presents the AUS and CT imaging features of two histopathologically suspected gastric plasmacytomas. Combining the four previous and two new cases, these tumors predominantly occurred in the greater curvature and pyloric antrum as solitary round masses connected to the submucosal or transmural layers. Pre- and post-contrast tissue attenuation (Hounsfield unit; HU) differences exceeded 40, with variable AUS echogenicity and echotexture. Imaging features may resemble those of spindle cell tumors, requiring histological and immunohistochemical examinations for definitive diagnosis.